2012
DOI: 10.1111/jop.12003
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the oral cavity by yeasts in patients with chronic renal failure undergoing hemodialysis

Abstract: The rate of colonization by yeasts in PCRFH was high, and there was variability in species distribution and antifungal susceptibility profile. These results are little known in this group of patients and are important for controlling the risk of developing invasive fungal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Our study showed a frequency of oral Candida colonization at 53.6%. In the literature, oral yeast colonization in HD patients has been detected between 39% and 43% (16). When compared with the literature, oral Candida colonization incidence has been found to be higher in our study than others.…”
Section: Discussionsupporting
confidence: 53%
“…Our study showed a frequency of oral Candida colonization at 53.6%. In the literature, oral yeast colonization in HD patients has been detected between 39% and 43% (16). When compared with the literature, oral Candida colonization incidence has been found to be higher in our study than others.…”
Section: Discussionsupporting
confidence: 53%
“…Godoy et al . investigated the frequency of oral yeasts in chronic renal insufficiency patients on haemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, the following changes in the oral microflora can be observed: the rate of colonization by yeasts is higher than normal, and variabilities in species distributions and antifungal susceptibility profiles can be observed. 4,5 The manifestations related to soft tissue involvement are summarized in Table 1.…”
Section: Oral Manifestationsmentioning
confidence: 99%